HUKUMAN PENCURIAN PADA QS. AL- MAIDAH AYAT 38 (STUDI TERHADAP PEMIKIRAN WAHBAH AZ-ZUHAILI DAN MUHAMMMAD SYAHRUR) - raof Bin Rased; Halimatussa’diyah Halimatussa’diyah; Anggi Wahyu Ari (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2021)
At the beginning of this study aims to understand about the punishment of theft in the present time where society considers this punishment is very cruel due to amputation that can make the perpetrator disabled for life, some even refuse and oppose when the punishment is to be implemented. The method used is the Comparative method, which is a method that compares the verses of the Qur'an with other verses, the verses of the Qur'an with the Hadith and the opinion of the commentator with other commentators. Muhammad Syahrur explained the theory of the limit, which is the position of the maximum limit, that is, the determination of punishment should not exceed the limit, but can be below it or remain at the maximum limit line. Wahbah Zuhaili said this punishment is a framework to educate and give lessons to the perpetrators and also to keep the community safe from something bad happening.